1990
DOI: 10.1111/j.1399-3011.1990.tb01294.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of insulin‐like growth factor I using N‐methyl pyrrolidinone as the coupling solvent and trifluoromethane sulphonic acid cleavage from the resin

Abstract: Insulin‐like growth factor I (IGF‐I), a protein of 70 amino acid residues and 3 cystine bridges, has been synthesized by two solid phase Boc methods. The first method used N‐methylpyrrolidinone as the solvent with single coupling cycles while the second synthesis used dimethylformamide and dichloromethane as the solvents with a double‐coupling protocol. In both cases, trifluoroacetic acid/trifluoromethanesulphonic acid cleavage of the peptide from the resin was employed. Purification of the cleavage products f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 17 publications
0
8
0
2
Order By: Relevance
“…A subsequent synthesis of IGF‐1 by Wallace et al . reported a yield of ~0.4% . More recently, the preparation of a fluorescently labeled IGF‐2 analog was published by Abell et al .…”
Section: The Chemical Synthesis Of Proinsulin Igf‐i and Igf‐iimentioning
confidence: 99%
See 1 more Smart Citation
“…A subsequent synthesis of IGF‐1 by Wallace et al . reported a yield of ~0.4% . More recently, the preparation of a fluorescently labeled IGF‐2 analog was published by Abell et al .…”
Section: The Chemical Synthesis Of Proinsulin Igf‐i and Igf‐iimentioning
confidence: 99%
“…The first syntheses of the IGFs were reported by Li and co-workers, who assembled the 70-residue IGF-1 in 1983 with a yield of~1% [102,103] and the 67-residue IGF-2 in 1985 with a yield of~2% [104,105]. A subsequent synthesis of IGF-1 by Wallace et al reported a yield of~0.4% [106,107]. More recently, the preparation of a fluorescently labeled IGF-2 analog was published by Abell et al [108].…”
Section: The Chemical Synthesis Of Proinsulin Igf-i and Igf-iimentioning
confidence: 99%
“…Although the Boc‐based ones have proven to be successful26, the Fmoc‐based ones have offered varying levels of success26–29. In general, the Fmoc‐based syntheses use polystyrene resins, such as the Wang resin, and differ in their approach in resolving undesired self‐association of the growing sequence, encompassing the use of Hmb‐amide protecting groups26, 27 Dmb‐protected dipeptides29, a mixture of DMF/NMP as solvent30, and/or high temperatures28, 31. However, using extreme conditions for amino acid couplings—especially high temperatures—can decrease the quality of the desired peptide, chiefly due to side reactions such as amino acid racemisation1.…”
Section: Introductionmentioning
confidence: 99%
“…The choice of hepatitis C virus envelope protein sites for scanning and the preparation of the peptide list were described elsewhere [7, 9]. The peptide synthesis from Fmoc-amino acids using DIPC as the condensation catalyst, as described in the “Mimotopes” manual and [22], was chosen as a standard procedure, except that 4-methyl-piperidine (4MPIP) was employed instead of piperidine [36, 37] and NMP was used as the Fmoc removal and amino acid attachment solvent instead of DMF [38]. …”
Section: Methodsmentioning
confidence: 99%